USM PREPARES FOR BUDGET CUTS; INCREASES PRODUCTIVITY, CREATIVITY AND AUSTERITY MEASURES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 28 October 2015 Universiti Sains Malaysia (USM) is planning and taking all the necessary steps in facing reduced allocations from the recentlyannounced National Budget 2016, including campuswide austerity measures involving the students, the continuing educational activities, raising productivity and other appropriate incomegenerating measures.